Teaching Presence: Co-Creating a Multi-National Online Learning Community in an Asynchronous Classroom - Leanne M. Dzubinski (Adult Education Research Conference, 2014)
Effective teaching presence in a multi-national online class involves building student confidence, affirming student voice, and the strategic use of groups. Effective instructor techniques include setting up the class, having ongoing public and private interaction with students, giving effective feedback, and valuing cultural differences.